Ameliorative Effect of Olea europaea Leaf Extract on Cisplatin-Induced Nephrotoxicity in the Rat Model - Ibrahim, Doa'a; Halboup, Abdulsalam; Al-Ashwal, Mohammed; Shamsher, Amani (Hindawi, 2023)
Background. Olea europaea leaf extract (OELE) has potential health benefits and protects against cytotoxicity. This study investigated the possible ameliorative effect of OELE on cisplatin-induced nephrotoxicity in rats. Methods. Rats were assigned into six groups; two groups received 150?mg/kg or 300?mg/kg of OELE, one group received a single dose of cisplatin (6?mg/kg) IP on the first day of the experiment, two groups received a single dose of cisplatin 150?mg/kg or 300?mg/kg of OELE on the first day then starting from the fifth day for 10 consecutive days, and one group acted as a control. Results and Conclusion. The findings showed that cisplatin-induced nephrotoxicity was evidenced by a significant increase in serum creatinine blood urea nitrogen (BUN) and a significant decrease in estimated creatinine clearance and potassium level, which corresponded with the alterations in the histopathology of the renal tissue. OELE significantly ameliorated the nephrotoxic effects of cisplatin as dose-dependent.